Socialisation professionnelle des directions d’établissement d'enseignement au Québec : tensions entre formation et autonomie professionnelle - Houssine Dridi (Éducation et Socialisation)
Even though the education faculties tried to resist, the professionalization finally came to the forefront in 2001 with a ministerial regulation setting the obligation of graduate training in school management. Guided in 2008 by a “reference of skills”, it is intended for the professional socialization of directors of educational institutions by endowing them with solid knowledge, both theoretical and practical and accompanying them in their professional integration. This contribution is based on a study conducted as part of a university-school board partnership. A questionnaire and some interviews with 70 institutional vice-principals were used to analyze the data, highlighting a difficulty in using university research results in practical settings and revealing a challenge with the design of the program, training, support arrangements and evaluation mechanisms. A reflection is emerging around the challenges of the improvement of training and professional socialization.